Variations in Mastery-Based Testing. Issue 8 (25th November 2020) - Harsy, Amanda
Abstract: As educators, it is important for us to recognize that our assessment methods affect student attitudes. If we want students to learn from their mistakes and counteract a fixed-mindset of learning, perhaps we should look at what we incentivize in the classroom. Some professors are attempting to counteract math and test anxiety, poor STEM retention, and a fixed-mindset of learning by using a new assessment model called "Mastery-Based Testing" (MBT). In MBT, students are given problems in which they can only receive full credit for the problem after they demonstrate mastery of the objective being tested. In this paper, we discuss different implementations of Mastery-Based Testing in a variety of courses. We also include student feedback from the survey data collected from MBT courses.